Defense Mechanisms of Marginalized People in the Novel Sisi Tergelap Surga by Brian Khrisna - Ninis Nur Mufidatul Khamdiyah; Alfian Setya Nugraha (Jurnal Pembelajaran Bahasa dan Sastra, 2026)
This study analyzes the defense mechanisms of marginalized characters in the novel Sisi Tergelap Surga by Brian Khrisna. The research was conducted as a library study without a specific location, using primary data in the form of the novel’s text and secondary data from books, journals, and relevant scientific articles. The population of the study includes all marginalized characters in the novel, while the sample was determined through excerpts depicting defense mechanisms. The researcher acted as the research instrument, assisted by a data recording guide using the read-and-record technique. Data analysis was carried out descriptively and qualitatively using the interactive model of Miles and Huberman, which includes data reduction, data display, and drawing conclusions. The results show that marginalized characters face social pressures, internal conflicts, and injustice by employing defense mechanisms such as repression, projection, rationalization, and displacement. Repression is shown through the suppression of feelings and experiences that cause anxiety, projection through the transfer of guilt and faults onto others, rationalization through logical justification of painful actions or conditions, and displacement through the venting of negative emotions toward safer targets. These defense mechanisms enable the characters to maintain psychological balance amid a life full of pressure, while also reflecting the social, economic, and structural impacts on the mental condition of marginalized groups. The findings contribute to the study of literary psychology, particularly regarding the representation of mental health among marginalized groups in contemporary Indonesian novels.